Women's Perspectives on Childbirth Care Services Leading to the Maternal Near-Miss event: a Qualitative Study - Zahra Moudi; Leyla Arabnezhad; AbouAli Vedadhir (Zanjan University of Medical Sciences and Health Services, 2022)
Background: Insufficient evidence exists regarding the causes of adverse birth outcomes among women with previous cesarean sections (C-Section). Objectives: This study aimed to explore women's perspectives on childbirth care services leading to maternal near-miss (MNM) events. Methods: Following a narrative design, 12 women with a previous C-section who had an episode of MNM during childbirth or postpartum period referring to a tertiary referral hospital in Zahedan city, Iran, were chosen using purposive sampling. Face-to-face interviews were used to collect data. Data were analyzed using the six-phase guide to thematic narrative analysis approach. Results: Two themes related to childbirth care services leading to maternal near-miss events were extracted: (1) 'Ineffective communication' (Ignoring the patient's words, Insensitive listener, and Non-critical thinking listener) and (2) 'Inappropriate care' (implementation of unnecessary or inappropriate care and early discharge). Conclusion: An audit system is necessary to provide objective information on the domains related to care provision and help timely feedback to healthcare providers to improve the quality of care.